Upaya American Israel Public Affairs Committee (AIPAC) terkait Keputusan Amerika Serikat untuk Memindahkan Kedutaan Besar Amerika Serikat di Israel dari Tel Aviv ke Yerusalem Tahun 2018 - Febriyanti, Gusti Ayu Lia; Kumala Dewi, Putu Ratih; Suwecawangsa, Adi Putra (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL), 2020)
ABSTRACT This research aims to explain AIPAC attempts in accomplishing their group’s interests through US’ foreign policy. The Researcher uses qualitative methods. The background of this research is AIPAC’s interest in recognizing Jerussalem as Israel’s capital. Upon the previous administrations, The US Government had failed to move US Embassy into Jerussalem until the administration JUR f Donald Trump issuing the policy of relocating US embassy into Jerussalem from Tel Aviv. The Researcher uses the concept of foreign policy and interest groups as the framework. The level of analysis used in this research is state level of analysis. This research perceives that AIPAC successfully performed their function, such as lobbying fuction and participating function as an interest group in US. While performing their attempts in accessing the policy makers and forming coalitions. AIPAC managed to influence the foreign policy of US Government in relocating US embassy from Tel Aviv to Jerussalem. Keywords : AIPAC, Interest Group, Foreign Policy, United States of America.